Systematic review and meta-analysis of enteric virus shedding in human excretionsResearch in context - Gang Zheng; Elana M.G. Chan; Alexandria B. Boehm (EBioMedicine)
Summary: Background: Wastewater-based epidemiology can inform the understanding of infectious disease occurrence in communities. Quantitative information on shedding of pathogen biomarkers in excretions that enter wastewater is needed to link measurements of pathogen biomarkers to rates of disease occurrence. Methods: We compile, summarise, and compare data on shedding of human norovirus, rotavirus, hepatitis A virus, and adenovirus group F in stool, vomit, urine, saliva, mucus, and sputum using a systematic review and meta-analysis approach. Findings: We provide summaries of measured concentrations of the viruses across excretions where data exist. We provide longitudinal shedding profiles in terms of concentrations and positivity rates. Duration of shedding and day of peak shedding are also provided. Interpretation: There are limited data available for excretions other than stool, and limited data available for adenovirus group F. The aggregated data provided herein can serve as model inputs to translate wastewater enteric virus biomarker concentrations to disease occurrence rates. The study highlights data gaps and research needs. Funding: This study was funded by a gift from the Sergey Brin Family Foundation to ABB.